Analisis Hukum Dalam Penetapan Pengadilan Agama Tentang Perwalian Anak Kandung Yang Masih Di Bawah Umur - Rexy Merchiano; Mohd. Syafariansyah; Erwan Effendi; Irman Ichandri; Sadli Sadli (Lex Stricta : Jurnal Ilmu Hukum, 2023)
The case for Petition for Guardianship Number 227/Pdt.P/2022/PA.Plg which was submitted to the Palembang Religious Court, in its ruling granted the petitioner's request by designating the Petitioner as the guardian of his biological child. Meanwhile, Article 47 of Law Number 16 of 2019 Concerning Marriage explains that 1) Children who have not reached the age of 18 (eighteen) years or have never been married are under the authority of their parents as long as they are not deprived of their authority. 2) Parents represent the child regarding all legal actions inside and outside the Court. So, actually to become guardians for their biological children in carrying out legal actions, parents do not need a guardianship stipulation from the Religious Courts. The research method in this research is normative legal research. The Panel of Judges considered that the purpose of the petitions was for the benefit of their children, taking into consideration the management of securities. Although, and the legal basis used by the Panel of Judges in deciding this case includes Law Number 16 of 2019 jo. Article 107 Complications of Islamic Law and Article 389 of the Civil Code. From this study, the procedure and determination of guardianship are in accordance with civil law based on the provisions of Article 345 of the Civil Code. The reason for the Petitioners in submitting the application for the determination of guardianship to the Court is to fulfill the requirements for the interests of taking care of the children's rights to the share of the assets inherited from their biological father.